Effectiveness of 2 interventions for independent oral feeding in preterms - María Fernanda Hernández Gutiérrez; N. Marta Díaz-Gómez; Alejandro Jiménez Sosa; José Miguel Díaz Gómez; Eduardo Domenech Martinez (Anales de Pediatría (English Edition), 2022)
Introduction: Oral feeding of preterm newborns (PTNB) is hampered by their immaturity and intercurrent diseases, which can prolong their hospital stay. The objective of this study was to assess the effectiveness of a program that combines tactile, kinesthetic and oral stimulation (T + K + OS) compared to another intervention based on exclusively oral stimulation (OS), in the time necessary to achieve independent feeding and hospital discharge. Patients and methods: A clinical study of 2 randomized groups (OS vs. T + K + OS) was carried out on 42 PTNB with gestational age between 27-32 weeks and birth weight > 900 g. The stimulation programs were carried out in sessions of 15 min, for 10 days. Results: The PTNBs in the T + K + OS group achieved independent oral feeding earlier, compared to the OS group (24.9 ± 10.1 vs. 34.1 ± 15.6 days, P = .02). An analysis of covariance was performed, which confirmed that the birth weight and gestational age covariates had significant effects on time to reach suction feeding (birth weight: F[1, 38] = 5.79; P = .021; gestational age: F[1, 38] = 14.12; P = .001) and that once its effect was controlled, the intervention continued to have a significant effect (F[1, 38] = 6.07; P = .018). The T + K + OS group, compared to the OS group, achieved an earlier hospital discharge (39 ± 15 vs. 45 ± 18 days), although the differences were not significant (P = .21). Conclusions: Combined therapies that include T + K + OS are more effective than OS alone, in order to achieve independent oral feeding in PTNBs. Resumen: Introducción: La alimentación oral de los recién nacidos pretérmino (RNPT) está dificultada por su inmadurez y enfermedades intercurrentes, lo que puede prolongar su estancia hospitalaria. El objetivo de este estudio fue valorar la efectividad de un programa que combina la estimulación táctil, kinestésica y oral (ET + K + O) frente a otro de estimulación oral sola (EO), en el tiempo necesario para lograr la alimentación independiente y el alta hospitalaria. Paciente y métodos: Estudio clínico de 2 grupos aleatorizados (EO vs. ET + K + O), realizado en 42 RNPT con una edad gestacional entre 27-32 semanas y un peso al nacimiento > 900 g. Los programas de estimulación fueron realizados en sesiones de 15 min, durante 10 días. Resultados: Los RNPT del grupo de ET + K + O consiguieron antes la alimentación oral independiente, en comparación con el grupo de EO (24,9 ± 10,1 vs. 34,1 ± 15,6 días, p = 0,02). Se realizó un análisis de covarianza, observando que las covariables PN y EG tuvieron efectos significativos en el tiempo hasta alcanzar la alimentación por succión (peso al nacimiento: F[1, 38] = 5,79; p = 0,021; edad gestacional: F[1, 38] = 14,12; p = 0,001) y que una vez controlado su efecto, la intervención seguía teniendo un efecto significativo (F[1, 38] = 6,07; p = 0,018). El grupo de ET + K + O, en comparación con el de EO, consiguió antes el alta hospitalaria (39 ± 15 vs. 45 ± 18 días), si bien la diferencia no fue significativa (p = 0,21). Conclusiones: Las terapias combinadas que asocian ET + K + O son más eficaces que la EO sola, para lograr la alimentación oral independiente en los RNPT.